Pengaruh Tingkat Pendidikan Orang Tua Dan Motivasi Terhadap Prestasi Belajar Produk Kreatif Kewirausahaan - Santi, Nur; Sumaryoto, Sumaryoto; Ahdiyat, Maman (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2025)
The aims of this research are 1). The effect of parents' education level on learning achievement. 2), The effect of motivation on learning achievement. 3). The influence of parents who have higher education on learning achievement. 4). The influence of parents who have low education on learning achievement. 5). The influence of parents who have a way of educating children properly and correctly. 6). The effect of parental attention in learning on learning achievement. The sample in this study was 83 students who were selected randomly. The method used in this study is a survey with a correlational technique. The results showed: 1). There is a significant influence on the level of parental education and motivation to learn together on the learning achievement of Creative Entrepreneurship products for private vocational high school students in East Jakarta. This is evidenced by the acquisition of the value of Sig. 0.000 < 0.05 and Fh = 14,807. 2). There is a significant influence on the level of parental education on the learning achievement of Creative Entrepreneurship products for private vocational high school students in East Jakarta. This is evidenced by the acquisition of the value of Sig. 0.049 < 0.05 and th = 1.998. 3). There is a significant influence of learning motivation on learning achievement of creative products of Entrepreneurship for Private Vocational High School students in East Jakarta. This is evidenced by the acquisition of the value of Sig. 0.000 < 0.05 and th = 4.914.